Análise do desempenho de um queimador infravermelho funcionando com gás liquefeito de petróleo e glicerina - Dantas, Marcello Araújo (2010)
The use of infrared burners in industrial applications has many advantages in terms of technical-operational, for example, uniformity in the heat supply in the form of radiation and convection, with greater control of emissions due to the passage of exhaust gases through a macro-porous ceramic bed. This paper presents an infrared burner commercial, which was adapted an experimental ejector, capable of promoting a mixture of liquefied petroleum gas (LPG) and glycerin. By varying the percentage of dual-fuel, it was evaluated the performance of the infrared burner by performing an energy balance and atmospheric emissions. It was introduced a temperature controller with thermocouple modulating two-stage (low heat / high heat), using solenoid valves for each fuel. The infrared burner has been tested and tests by varying the amount of glycerin inserted by a gravity feed system. The method of thermodynamic analysis to estimate the load was used an aluminum plate located at the exit of combustion gases and the distribution of temperatures measured by a data acquisition system which recorded real-time measurements of the thermocouples attached. The burner had a stable combustion at levels of 15, 20 and 25% of adding glycerin in mass ratio of LPG gas, increasing the supply of heat to the plate. According to data obtained showed that there was an improvement in the efficiency of the 1st Law of infrared burner with increasing addition of glycerin. The emission levels of greenhouse gases produced by combustion (CO, NOx, SO2 and HC) met the environmental limits set by resolution No. 382/2006 of CONAMA